Patient Portal Use and Care Utilization Among Hospitalized Children - Michael J. Luke; Yinlu Zhu; Courtney B. Wolk; Stephanie G. Menko; Danielle Capriola; Kate Fuller; Philip V. Scribano; Christopher P. Bonafide; Aditi Vasan (Hospital Pediatrics, 2026)
OBJECTIVE Patient portals allow patients and caregivers to better engage with health care. Disparities in portal use among high-risk populations, like hospitalized children, could limit their benefits. Additionally, little is known about the association between pediatric portal usage and acute care utilization. PATIENTS AND METHODS We conducted a cross-sectional analysis to identify disparities in portal activation and use among patients admitted to 2 children’s hospitals from 2022 to 2024. We described unadjusted patterns of portal use and then used multivariable regression to examine the association between portal activation and use before, during, and after hospitalization and patient-level factors, household-level factors, and population-level factors, as well as critical care admissions, hospital length of stay (LOS), and 30-day readmissions. RESULTS Among 40 371 hospitalized patients, 93% had activated portal accounts. Patients who identified as non-Hispanic Black, were publicly insured, had a household language other than English, and lived in lower-opportunity neighborhoods had significantly lower odds of portal activation and use before, during, and after hospitalization. Patients with portal use before hospitalization had decreased odds of critical care admission (odds ratio, 0.64; 95% CI, 0.58–0.70) and shorter LOS (incident rate ratio, 0.74; 95% CI, 0.69–0.79), with no difference in readmissions. CONCLUSIONS Despite high rates of portal activation in our sample, we observed persistent disparities in portal activation and use. Associations between portal activity and acute care utilization are complex and merit further investigation. Efforts to promote equitable portal usage among hospitalized children should focus on families who are publicly insured, prefer languages other than English, and live in lower-opportunity neighborhoods.